An empirical test of the asymmetric models on innovative activity: who invests more into R&D - the incumbent or the challenger? - Dirk Czarnitzki; Kornelius Kraft (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2000)
The theoretical discussion concerning the question whether the incumbent or the (potential) entrant invests more into R&D has attracted considerable interest. This paper reports the results of an empirical study on this question using data of about 3500 German firms over the years 1992 to 1995. The survey explicitly asks the firms for their motives to undertake innovative activity. It is thus possible to take account of intended, not just completed, market entry. It turns out that the challenger invests more into R&D in order to enter a new market than the incumbent. Thus, the patent racing model by Reinganum and others seems to characterize innovative activity more accurately than the competing auction model of Gilbert and Newbery. We use a heteroscedastic tobit as well as a tobit model with selectivity in order to deal with the econometric problems of double censoring.
Keywords: O31; O32; L12; 330; Innovative Activity; Patent Races; Uncertainty; Incumbent versus Entrant; Tobit with Selectivity; Innovationswettbewerb; Markteintritt; Industrielle Forschung; Forschungskosten; Patent; Schätzung; Theorie; Deutschland